2013
DOI: 10.1002/star.201300117
|View full text |Cite
|
Sign up to set email alerts
|

Radiation synthesis and characterization of starch‐based hydrogels for removal of acid dye

Abstract: A series of hydrogels based on starch, acrylic acid (AAc) and 2‐hydroxyethyl methacrylate (HEMA), namely AAc/starch and AAc/HEMA/starch hydrogels were synthesized by gamma radiation and used to adsorb acid fast red dye from aqueous solution. Alkali treatment of AAc/starch hydrogels to improve their ionic character was evaluated. The structure and surface morphology of prepared hydrogels were confirmed by Fourier transfer infrared spectra and SEM, respectively. The results indicated that the diffusion of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For instance, Guo et al [22] synthesized a crosslinked porous starch and found that its adsorption capacity of product for methylene blue (MB) can reach 9.46 mg g −1 , which was much higher than that of native starch. Mahmoud et al [23] prepared a series of starch-based gels and used them to adsorb acid dye. Despite the progress on using starch as an adsorbent in recent years, the starch-based adsorbents generally suffer from several drawbacks such as low adsorption capacity [24], complex separation process and poor reusability [25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Guo et al [22] synthesized a crosslinked porous starch and found that its adsorption capacity of product for methylene blue (MB) can reach 9.46 mg g −1 , which was much higher than that of native starch. Mahmoud et al [23] prepared a series of starch-based gels and used them to adsorb acid dye. Despite the progress on using starch as an adsorbent in recent years, the starch-based adsorbents generally suffer from several drawbacks such as low adsorption capacity [24], complex separation process and poor reusability [25].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the removal percentage increases with the increase in pH of the medium of all investigated samples and the maximum value are got at pH 10.5. It is well known that the extent of adsorption is highly varied according to the adsorbent functional groups [42]. MB is cationic dye.…”
Section: Adsorption Studymentioning
confidence: 99%
“…SWA products are polymeric materials which have been utilized in agriculture as a means to store and control the release of water, fertilizer, and pesticide, thereby increasing plant performance and survivability while minimizing agro‐environmental pollution 3,4 . These polymers can also be used to purify chemically contaminated water through sorption of toxic heavy metals and dyes 5–8 . Despite these favorable attributes, recent studies have drawn attention to how some commercial SWAs pose environmental problems as they are non‐biodegradable and not suitable for use in agricultural soil 9–11 .…”
Section: Introductionmentioning
confidence: 99%